Reskilling and Upskilling: Survival Strategies Amid Global Competency Shifts - Nico Kosasih (PT. Anagata Sembagi Education, 2025)
This study explores the role of reskilling and upskilling as survival strategies in navigating accelerated global competency shifts driven by technological innovation, globalization, and industrial transformation. Using a qualitative, descriptive-analytical literature review, the research synthesizes findings from reputable academic sources, policy documents, and institutional reports to map the driving forces, challenges, and strategic approaches to workforce adaptability. Results indicate that reskilling acquiring entirely new skill sets and upskilling enhancing existing competencies are complementary approaches essential for bridging skills gaps, enhancing workforce readiness, and sustaining organizational competitiveness. The study identifies significant research gaps, particularly the scarcity of empirical studies in developing economies and the limited integration of socio-economic factors into skill development frameworks. This research offers a novel, context-sensitive model that incorporates technological, economic, and socio-cultural dimensions, providing theoretical contributions and practical implications for policymakers, organizations, and educational institutions in fostering future-ready workforces.